Letter from Robert Cant to his family - Cant, Robert, engineer; Cant family (1945)
An air-letter from Robert to his family, dated 11th April 1945, in which he describes his work in Burma repairing rail lines, and the dreadful living conditions in their camp; he reassures them of his safety.
Keywords: Cant, Robert, -- engineer -- Correspondence; World War, 1939-1945 -- Campaigns -- Burma